1997
DOI: 10.1073/pnas.94.8.3753
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin mRNA levels are up-regulated by free cholesterol and down-regulated by oxysterols in fibroblast monolayers

Abstract: In conf luent fibroblast monolayers, an increase in the selective uptake of free cholesterol (FC) from plasma low density lipoprotein (LDL) was accompanied by an increase in FC eff lux. The rate of FC eff lux was proportional to the FC content of the cell surface caveolae and to mRNA levels of caveolin, an FC-binding protein of caveolae. Inhibitors of LDL-FC internalization reduced the increase in caveolin mRNA levels and FC eff lux. Oxysterols reduced caveolin mRNA levels, as well as transport of FC to the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
172
3
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 39 publications
13
172
3
4
Order By: Relevance
“…That oxide does not inhibit nitric oxide synthesis and does not act on estrogen receptors, but has a cytotoxic effect on endothelial cells 47,48 . Fielding et al 29 reported that cholesterol oxides reduce caveolin mRNA, the transportation of free cholesterol to cell surface, and free cholesterol efflux. Caveolae are probable intermediates of free cholesterol efflux via HDL 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That oxide does not inhibit nitric oxide synthesis and does not act on estrogen receptors, but has a cytotoxic effect on endothelial cells 47,48 . Fielding et al 29 reported that cholesterol oxides reduce caveolin mRNA, the transportation of free cholesterol to cell surface, and free cholesterol efflux. Caveolae are probable intermediates of free cholesterol efflux via HDL 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Fielding et al 29 reported that cholesterol oxides reduce caveolin mRNA, the transportation of free cholesterol to cell surface, and free cholesterol efflux. Caveolae are probable intermediates of free cholesterol efflux via HDL 29 . The presence of oxysterols in HDL reduces the capacity of that lipoprotein to stimulate cholesterol efflux 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mitogen-activated protein kinase pathway extracellular signalregulated kinase (ERK) has been shown to control caveolin-1 expression at the transcriptional level in NIH 3T3 cells (10), whereas activation of Src family kinases transcriptionally decreases caveolin-1 expression (2). In addition, caveolin-1 transcription is up-regulated by sterol regulatory elementbinding protein-1 in response to free cholesterol, which results in caveolae formation and increased cholesterol efflux (12,13). Conversely, high density lipoprotein exposure reduces caveolin-1 expression and prevents the uptake of oxidized cholesterol (14).…”
mentioning
confidence: 99%
“…Although specific experiments have to be performed to understand the precise effects of oxysterols in HSA secretion, several in vitro experiments have already shown that oxysterols can reduce protein expression and mRNA levels in cultured cells. 46,47 Different transcription factors have been shown to be involved in the sterol-mediated regulation of genes involved in cholesterol homeostasis. Most extensive studies have been carried out on the sterol regulatory element binding proteins 1 and 2, which are responsible for the sterol-mediated suppression of the LDL receptor, 3-hydroxy-3-methylglutaryl coenzyme A synthase, and fatty acid synthase genes.…”
Section: Discussionmentioning
confidence: 99%